1982
DOI: 10.1007/bf01276577
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine, a potent selective long-acting inhibitor of synaptosomal 5-HT uptake in mice

Abstract: SummaryThe high-affinity uptake of tritium labelled tryptophan (TRY), 5-hydroxytryptophan (5-HPT), 5-hydroxytryptamine (5-HT), noradrenaline (NE), dopamine (DA), glycine and glutamic acid into forebrain synaptosomes, and serum 5-HT concentrations were studied in mice. In vitro the rank order of potency (the concentration causing 50 percent uptake inhibition) of seven inhibitors of 5-HT uptake was paroxetine >citalopram > femoxetine >fluoxetine > alaproclate _->imipramine > zimelidine. Paroxetine was a weak inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…These data are broadly in agreement with the findings of Hyttel (1982), Claassen (1983) and Wong et al (1983). Magnusson et al (1982) have previously shown that paroxetine potently and selectively inhibits [3H]-5-HT uptake in mouse brain after intraperitoneal administration. It has now been demonstrated that using a similar ex vivo technique in rats, paroxetine is a potent inhibitor of [3H]-5-HT uptake into hypothalamic synaptosomes after oral administration (EDso = 1.9 mg/kg PO).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…These data are broadly in agreement with the findings of Hyttel (1982), Claassen (1983) and Wong et al (1983). Magnusson et al (1982) have previously shown that paroxetine potently and selectively inhibits [3H]-5-HT uptake in mouse brain after intraperitoneal administration. It has now been demonstrated that using a similar ex vivo technique in rats, paroxetine is a potent inhibitor of [3H]-5-HT uptake into hypothalamic synaptosomes after oral administration (EDso = 1.9 mg/kg PO).…”
Section: Discussionsupporting
confidence: 82%
“…The selectivity of paroxetine for inhibition of [3H]-5-HT uptake in vitro and ex vivo has been shown previously using mouse brain synaptosomes (Magnusson et al 1982). Some of the data reported here have been presented previously in preliminary form (Nelson etal.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Given a paroxetine plasma free fraction of 5% (Hyttel 1994), a plasma concentration of 2.9€0.7 ng/ ml would correspond to an intracerebral free paroxetine concentration of 0.38 nM. This value is in close agreement with published in vitro paroxetine K d values for SERT in human brain (0.15 nM; Laruelle et al 1988), and in rodent brain (0.4 nM; Magnussen et al 1982). This conclusion contrasts with the conclusions of Meyer et al (2001), who noted that SERT occupancy observed with PET was lower than predicted based on the in vitro K d of paroxetine.…”
Section: Discussionsupporting
confidence: 79%